Konstrukcija romskega političnega predstavništva - Komac, Miran (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2007)
The article deals with the ways of (re)constructing of Roma ethnic community, from the amorphous mass of individuals on the margins of the Slovene society to a national minority. Roma councillors are placed to the forefront of this transfiguration. Political activists may be an important factor in the awareness of the Roma community in Slovenia about their adherence to a common nation, regardless of their territory of settlement; the awareness of their being a national minority in Slovenia, and consequently being entitled to the same extent of rights and duties as the Italian and Hungarian national minorities. The basic purpose of the training of Roma councillors for effective political work, in which members of the majority nation can actively participate, is the building-up of the awareness that in order to eliminate their marginal social status, the dealing with Roma in Slovenia needs to be altered - from treating the Roma community as a marginalized social group to treating them as a national minority.
Keywords: Slovenia; Slovenija; etnične skupine; narodne manjšine; Romi; politična participacija